(3QSGdI aj GdefWbs
(3ChdgG (B:s
(3bGd GdTGQM cd eaghe EPG fSH Edi eaghe BNQ dGHO Cf hGdeagheGJ GdJUOjbjI heG ai McegG ef GdeagheGJ s
(3BNQgG (B:s
(3hCeKGd gPg GdCMcGe cKQg dGjNai hgPG BNQ eG bUOfG EjQGOg ai JMbjb UGMH GddH hGdMeO ddg Ydi Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs